The Perfect Politician - Lechterman, Theodore (Oxford University Press, 2024)
Ideas for integrating AI into politics are now emerging and advancing at accelerating pace. This chapter highlights a few different varieties and shows how they reflect different assumptions about the value of democracy. We cannot make informed decisions about which, if any, proposals to pursue without further reflection on what makes democracy valuable and how current conditions fail to fully realize it. Recent advances in political philosophy provide some guidance but leave important questions open. If AI advances to a state where it can secure superior political outcomes, leading perspectives in political philosophy suggest that democracy may become obsolete. If we find this suggestion troubling, we need to put the case for democracy on stronger foundations.
Keywords: Artificial intelligence; AI; Politicians; Politics; Elections; Democracy; Voting; Algocracy; Democratic theory; Political philosophy; ODS 16 - Paz, justicia e instituciones sólidas